2015
DOI: 10.1126/scisignal.aab2677
|View full text |Cite
|
Sign up to set email alerts
|

Instructive roles for cytokine-receptor binding parameters in determining signaling and functional potency

Abstract: The affinity of cytokine-receptor complexes on the cell surface is often poorly predictive of functional potency. To address this conundrum, we explored the inter-relationships of receptor binding to a wide range of downstream functional metrics for a prototypical cytokine, Interleukin-13 (IL-13), through structure-based engineering of agonists covering a spectrum of binding strengths for IL-13Rα1. Surprisingly, engineered IL-13 agonists spanning a broad affinity range exhibited similar potencies of STAT6 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 61 publications
4
72
0
Order By: Relevance
“…Recent studies have demonstrated the value of using total internal reflection fluorescence (TIRF) microscopy of labeled receptor molecules on the cell surface to visualize cytokine receptor dimerization dynamics and activation (Moraga et al, 2015a; Moraga et al, 2015b; Wilmes et al, 2015). We reasoned that probing the assembly of EPOR at the single molecule level could provide insight into mechanisms underlying the altered activity of the R150Q EPO mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated the value of using total internal reflection fluorescence (TIRF) microscopy of labeled receptor molecules on the cell surface to visualize cytokine receptor dimerization dynamics and activation (Moraga et al, 2015a; Moraga et al, 2015b; Wilmes et al, 2015). We reasoned that probing the assembly of EPOR at the single molecule level could provide insight into mechanisms underlying the altered activity of the R150Q EPO mutant.…”
Section: Resultsmentioning
confidence: 99%
“…However, in order to maximally harness the therapeutic potential of TSLP-mediated signalling, it will be essential to dissect the structural and mechanistic basis for its bioactivity. Recent efforts that have leveraged mechanistic and structure-based considerations of cytokine-mediated receptor activation, have led to the development of engineered IL-2, IL-4 and IL-13 variants with drastically improved therapeutic efficacy and specificity, illustrating the power of consolidating such approaches in the development of tailor-made biologics565758. In this study we have employed an integrative approach, including structural data at high-resolution, to propose a mechanistic blueprint for the activation and antagonism of the pro-inflammatory complex mediated by human TSLP.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of STAT1 in the HeLa cells was analyzed by flow cytometry, as previously described ( 54 ). The HeLa cells were stimulated with 0.01, 0.1, 1, and 10 nM IFNα2.…”
Section: Methodsmentioning
confidence: 99%